Agricultural Greenhouse Gas Emissions: Ukrainian Involvement in the Global Ecological Challenge - Vasylieva, Natalia; Васильєва, Наталя Костянтинівна; Sytnyk, Svitlana; Ситник, Світлана Анатоліївна (Каунаський технологічний університет, 2019)
Greenhouse gas emission is a global ecological challenge since it affects climate change and complicates providing food security. The performed research focused on Ukrainian ranking among the world greenhouse gas emitters offering a multi-criteria evaluation of total greenhouse gas quantities in CO2 equivalent, per capita and per km2 of countries’ land territories. To explore agricultural greenhouse gas emission at the domestic level, we studied regional contributions by basic source categories such as enteric fermentation, manure management, and synthetic fertilizers. To improve such standing, the conducted investigation specified the EU Member States which match the Ukrainian condition by shares of greenhouse gas emissions and outputs in animal and crop sectors. Емісія ПГ є глобальною проблемою, що впливає на зміну клімату та ускладнює підтримку продовольчої безпеки. Проведене дослідження позиціонувало Україну серед світових емітентів ПГ за критеріями загальних викидів у CO2 еквіваленті, на особу та на km2 території країни. Було розглянуто регіональне поширення емісії ПГ від ферментації, гною та мінеральних добрив у сільському господарстві. Для поліпшення ситуації визначено прийнятні до впровадження в Україні зразки з аграрного сектору ЄС порівняні за емісією ПГ та виробництвом продукції рослинництва і тваринництва.
Аграрна емісія парникового газу: залучення України до глобальної екологічної проблеми
Keywords: agricultural GHG emissions; аграрна емісія ПГ; multi-criteria ranking; мультикритеріальне ранжування; GHG distribution by regional sources; розподіл ПГ за регіональними джерелами; GHG mitiga- tion in the EU agriculture; зниження емісії ПГ в аграрному секторі ЄС